Synthesis, Characterization, and Theory of [9]-, [12]-, and [18]Cycloparaphenylene: Carbon Nanohoop Structures - Jasti, Ramesh (American Chemical Society, 2008)
[Image: see text] The first synthesis and characterization of [9]-, [12]-, and [18]cycloparaphenylene was demonstrated utilizing a novel aromatization reaction. We refer to these fascinating structures as “carbon nanohoops” due to their structural similarity to carbon nanotubes. Additionally, we have utilized computational methods to understand the unique properties of these fully conjugated macrocycles.